Survival of selected pathogens in dried shrimp (Penaeus sp.) during storage at room temperature - Diloy, Marecela L.; Alabastro, Estrella F. (1992)
Market samples of dried shrimps totaling nine (9) in all and weighing 500 grams each were purchased at Divisoria. Of the nine samples, four were contaminated with Salmonella sp. and four were positive for Staphylococcus. The Salmonella isolate which manifested the same characteristics to Salmonella paratyphi A and Shigella sonnei, and the Staphylococcus isolate which manifested the same characteristics as Staphylococcus aureus, were used in the survival study. When inoculated in dried shrimps and kept at varying Aw level, namely, 0.680-0.690, 0.710-0.720 and 0.780-0.790, the microbial population decreased on storage. The Staphylococcus isolate from hibe and pure culture of Staphylococcus aureus ATCC 6538P survived bbetter than the Salmonella isolate from shrimp and the pure culture of Salmonella typhi (Schroeter). The survival of the two Staphylococci appears to be unaffected by Aw while that of Salmonellae seems to be shorter at higher Aw's. Statistical analysis, however, did not show that Aw within the range of 0.680 to 0.790 has any significant effect on the survival of the organisms. On the 8th week of storage, the color of the shrimp became light yellow and light brown when kept at Aw 0.725 and 0.685. The shrimp samples that were maintained at Aw 0.790 became moldy on the 8th week of storage.
Computer print-out (photocopy).
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Pathogenic microorganisms; Salmonella; Shrimps